Determinantes da confiança do consumidor: uma análise da dinâmica de política monetária no Brasil - Caetano, Rafaela Maiara (2017)
It is increasingly visible how emotional and psychological factors influence the decision-making of economic agents. Thus, confidence indicators have been gaining analytical importance in the last decades by measuring precisely these qualitative factors in their calculation. The objective of this study is to investigate the determinants of consumer confidence in Brazil, as well as the effects of monetary policy dynamics on this confidence. The applied econometric methodology involves Autorregressive Distributed Lag (ARDL) allied to the cointegration approach, for monthly data between January 2003 and December 2016. The empirical results suggest that there is a long-term relationship between the consumer confidence index and the other analyzed variables. In relation to short-term dynamics, the error correction mechanism varies between 1.9% and 8.7%, depending on the estimated model. This suggests that economic variables influence consumer confidence, and when this confidence is put in check, it recovers in a time-consuming manner.